Ted-Ed Animated Videos’ Impact on Vocabulary Gain of Indonesian EFL Middle Schoolers - Kirana, Laksita Indah; Iswati, Henny Dwi (RETAIN : Journal of Research in English Language Teaching, 2023)
Vocabulary is one of the essential components of language learning and a primary key for effective communication in foreign language learning. Nowadays, audiovisual content has been well-known for enhancing students’ English skills. Previous studies primarily investigated the effect of audiovisual material on students’ speaking or listening skills development for high schoolers and college students. Subsequently, this study examined the impact of integrating visual-auditory material on Indonesian EFL middle schoolers’ vocabulary acquisition using TED-Ed animation videos, which were conducted with a quantitative approach and applied a one-group pretest-posttest design. The participants involved in this study were 24 students in the 8th grade at a private middle school in Surabaya that were treated with TED-Ed videos assessing their vocabulary knowledge. The videos applied for the treatment process have been filtered to relate to the personal recount text chapter in the 2013 curriculum and adjusted for eighth graders. This study found a significant improvement in students’ vocabulary acquisition, with a t-test result of 8.60 (≥ t table: 2.06). Overall, the posttest scores were higher than the pretest, indicating a positive impact on vocabulary learning. Furthermore, based on the findings, the researchers concluded that TED-Ed is a beneficial platform for enhancing EFL students’ learning.